2012
DOI: 10.1007/s00266-012-9913-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Relation to Age in Aesthetic Facial Surgery

Abstract: BackgroundSmoking is a major cause of premature facial aging. Skin aging in general, often accompanied by wrinkling and furrowing, plays a significant role in the decision to undergo aesthetic surgery. Smoking may therefore be related to the demand for cosmetic surgery. This study aimed to compare smoking habits with respect to a standard cosmetic procedure (blepharoplasty) in the general population and to evaluate whether the age at surgery differs between smokers and nonsmokers.MethodsA questionnaire was sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Významný rozdiel vo veku bývalých fajčiarov a nefajčiarov nebol zaznamenaný. Predpokladá sa, že tieto rozdiely vo veku paci-entov boli spojené so škodlivými účinkami cigaretového dymu na pokožku tváre (26).…”
Section: Zmeny Na Koži Vyvolané Fajčenímunclassified
“…Významný rozdiel vo veku bývalých fajčiarov a nefajčiarov nebol zaznamenaný. Predpokladá sa, že tieto rozdiely vo veku paci-entov boli spojené so škodlivými účinkami cigaretového dymu na pokožku tváre (26).…”
Section: Zmeny Na Koži Vyvolané Fajčenímunclassified
“…All authors read and approved the final manuscript. On the contrary, A.Elzen et al [15] conducted a study showed that the smokers group underwent blepharoplasty surgery 3.7 years earlier than the ex-smokers group, and 3.5 years earlier than the never-smokers group. Their study showed no significant difference between the ex-smokers group and the never-smokers group.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…The appearance of wrinkles and skin spots, hair thinning, baldness and the appearance of gray hair are phenomena related to aging and should be registered during the examination (Black, Aggrawal and Payne-James, 2010;Ichibori et al, 2014;Ramos and Miot, 2015;Ko, Korn and Kikkawa, 2017;Tsuboi et al, 2019;York et al, 2020). Some signs of senescence can also be seen in the eyes such as senile arch, dermatochalasis, pterygeum and pinguecola (Atchison et al, 2008;Deliaert et al, 2012;Grossniklaus et al, 2012;Jacobs et al, 2014;Song et al, 2017;Rezvan et al, 2018;Wanzeler et al, 2019). Such phenomena are complex and require care as they also reflect genetic, environmental, and pathological influences.…”
Section: Discussionmentioning
confidence: 99%